2005
DOI: 10.1371/journal.pbio.0030087
|View full text |Cite
|
Sign up to set email alerts
|

Adult Murine Skeletal Muscle Contains Cells That Can Differentiate into Beating Cardiomyocytes In Vitro

Abstract: It has long been held as scientific fact that soon after birth, cardiomyocytes cease dividing, thus explaining the limited restoration of cardiac function after a heart attack. Recent demonstrations of cardiac myocyte differentiation observed in vitro or after in vivo transplantation of adult stem cells from blood, fat, skeletal muscle, or heart have challenged this view. Analysis of these studies has been complicated by the large disparity in the magnitude of effects seen by different groups and obscured by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 40 publications
0
54
0
5
Order By: Relevance
“…Although SM are not endowed with the potential to differentiate into cardiomyocytes, [6] expression of cardiac specific genes was surprisingly detected in SM and differentiated cells such as troponin I (TNNC1) [38], cardiac specific troponin T (TNNT2) [39], cardiac troponin I (TNNI3) and β-myosin heavy chain (MYH7) albeit at low levels (0.3-1% of cardiomyocytes in comparison with cardiomyocytes). These findings suggest that SM could contain a genetic program that, under specific circumstances, would allow them to partially differentiate into cardiac muscle or at least that a population of cells within the myoblast pool could have this potential [27].…”
Section: Discussionmentioning
confidence: 92%
“…Although SM are not endowed with the potential to differentiate into cardiomyocytes, [6] expression of cardiac specific genes was surprisingly detected in SM and differentiated cells such as troponin I (TNNC1) [38], cardiac specific troponin T (TNNT2) [39], cardiac troponin I (TNNI3) and β-myosin heavy chain (MYH7) albeit at low levels (0.3-1% of cardiomyocytes in comparison with cardiomyocytes). These findings suggest that SM could contain a genetic program that, under specific circumstances, would allow them to partially differentiate into cardiac muscle or at least that a population of cells within the myoblast pool could have this potential [27].…”
Section: Discussionmentioning
confidence: 92%
“…The preplate technique, which is used to isolate cells according to variations in adhesion ability among different cell populations, [12][13][14][15]20,21 , showed different , and possessed a high myogenic potential both in vitro and in vivo, but could not undergo long-term self-renewal. Conversely, the LacZ-negative population, which possessed the ability to undergo long-term expansion, was highly positive for the stem cell markers CD34 (74.7%) and Sca-1 (98%; 74.5% Sca-1/CD34 doublepositive) and could not undergo myogenic differentiation in vitro and in vivo unless transduced with a retrovirus to express Pax7.…”
Section: Discussionmentioning
confidence: 99%
“…3 Our laboratory, as well as others, have shown that the slowly adhering cells (SACs) appear to be less committed to the myogenic lineage than fast-adhering cells. 3,[12][13][14][15] Following a preplate technique, only fast-adhering populations were obtained from Pax7 lacZ/lacZ mice. Furthermore, MDSC-like cells, which usually appear in the slowly adhering population in wild-type animals, appeared in our earlier preplate fractions from Pax7 lacZ/lacZ mice.…”
Section: Myogenic Cells Can Be Isolated From Pax7-deficient Skeletal mentioning
confidence: 99%
“…
AbstractAn emerging concept is that the mammalian myocardium has the potential to regenerate, but that regeneration might be too inefficient to repair the extensive myocardial injury that is typical of human disease [1][2][3][4][5][6][7][8] . However, the degree to which stem cells or precursor cells contribute to the renewal of adult mammalian cardiomyocytes remains controversial.
…”
mentioning
confidence: 99%